DEVELOPMENT OF ELECTRONIC-DIDACTIC CAPABILITIES FOR IMPROVING THE METHODOLOGICAL TRAINING OF FUTURE PRIMARY SCHOOL TEACHERS (American Journal of Pedagogical and Educational Research, 2025)
The article examines the theoretical foundations of problem-based learning, the development of electronic and didactic opportunities for improving the methodological training of future primary school teachers in higher education institutions and, at the same time, the use of problem-based learning in mathematics lessons. Improving Blended Learning Methods in Digital Learning Environments The article highlights the content of the use of digital technologies in the process of expanding the possibilities of independent learning in digital education, and also determines the level of effectiveness of the results obtained on the basis of experiments.